2013
DOI: 10.4236/cn.2013.53b2117
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Energy Efficiency in Cellular Networks

Abstract: With the continuous increase of user requirement, the Information and Communication Technology (ICT) has developed rapidly. As a result, both capacity and coverage performances have been improved, and at the same time, the communication networks have been more energy-intensive. In order to improve the energy efficiency of cellular networks, the green communication must be realized in the future networks. In this article, we present a short survey on energy-efficient technology of cellular networks. Moreover, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In the current Information and Communication Technology (ICT) industry there is a dire need to design energy or power efficient systems. Power efficiency can be achieved by having energy efficient architectures, energy efficient resource management, and by utilizing energy efficient radio technologies [22][23]. Utilizing simultaneous connections in addition to deploying small cells help in increasing the coverage of the network.…”
Section: Proposed Performance Metricmentioning
confidence: 99%
“…In the current Information and Communication Technology (ICT) industry there is a dire need to design energy or power efficient systems. Power efficiency can be achieved by having energy efficient architectures, energy efficient resource management, and by utilizing energy efficient radio technologies [22][23]. Utilizing simultaneous connections in addition to deploying small cells help in increasing the coverage of the network.…”
Section: Proposed Performance Metricmentioning
confidence: 99%
“…For green wireless communication, energy-efficient radio technologies have been presented in [12], where the issues on channel feedback information and CSI feedback overhead have been addressed to improve the energy efficiency. In [13], it was shown that the spectral efficiency and energy efficiency can be affected by channel feedback information in wireless multiple-input multiple-output transmission.…”
Section: Related Workmentioning
confidence: 99%
“…For Rayleigh fading channels (i.e., m k,n = 1 for all k and n), using Equations (6) and (12), the closed-form expression for η k,l k in Equation (5) can be simplified as follows:…”
Section: End-to-end Snr Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this energy consumption is continuously increasing at a rate of 15% per year. Especially, when smart grids are massively deployed, the energy consumption of AMI networks may intensify the issue [26]. Therefore, energy efficiency may be a new issue for AMI networks, which may pose new practical issues.…”
Section: Introductionmentioning
confidence: 99%